2004
DOI: 10.1007/s11661-004-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of coarsening, recrystallization, and morphology of microstructure in Al-Sc-(Zr)-(Mg) alloys

Abstract: Minor additions of Sc are effective in controlling the recrystallization resistance of 5xxx, 2xxx, and 7xxx aluminum. The addition of Sc to aluminum results in the rapid precipitation of homogeneously distributed Al 3 Sc dispersoids, which are coherent with the matrix and have the L1 2 structure. The presence of Al 3 Sc dispersoids increases the recrystallization resistance of wrought alloys. The higher coarsening rate of Al 3 Sc compared to that of Al 3 Zr may limit its applications as a single ancillary addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 17 publications
4
59
0
1
Order By: Relevance
“…The resulting misfit at the relevant annealing temperatures 773-823 K yields a calculated critical radius between 23-26 nm for Al 3 Sc [using Eq. (B3)], agreeing well with our experimentally observed range of 20-30 nm and the previously reported values [48,[50][51][52][53][54][55]. The critical particle size is found to increase with temperature, a trend consistent with the Al/Al 3 Sc lattice misfit which decreases with temperature.…”
Section: A Correlation Of Experimental Diffusion Trends and Precipitsupporting
confidence: 90%
“…The resulting misfit at the relevant annealing temperatures 773-823 K yields a calculated critical radius between 23-26 nm for Al 3 Sc [using Eq. (B3)], agreeing well with our experimentally observed range of 20-30 nm and the previously reported values [48,[50][51][52][53][54][55]. The critical particle size is found to increase with temperature, a trend consistent with the Al/Al 3 Sc lattice misfit which decreases with temperature.…”
Section: A Correlation Of Experimental Diffusion Trends and Precipitsupporting
confidence: 90%
“…Такое поведение сплава, по всей видимости, обусловлено активизацией процессов динамической рекристаллизации с ростом температуры испытания. Указанная немонотонная за-висимость положения оптимума сверхпластичности от температуры деформации вызвана тем, что присут-ствующие в сплаве нанодисперсные алюминиды пере-ходных металлов, Al 3 (Sc,Zr), обладают довольно высо-кой термической стабильностью лишь до температур 450-475°C [20,21]. Поэтому, когда плотность этих частиц наибольшая, и они когерентны матрице (что имеет ме-сто при низких температурах испытаний), то, взаимо-действуя с решеточными дислокациями, такие частицы интенсивно подавляют процессы возврата и рекристал-лизации, препятствуя тем самым формированию одно-родной мелкозернистой структуры в процессе сверхпла-стической деформации.…”
Section: результаты исследования и их обсуждениеunclassified
“…Al-Sc systems in terms of decreasing the coarsening rate [72,107], increasing the strength and the recrystallization resistance [23,113,114].…”
Section: Al-sc-zr Ternary Alloysmentioning
confidence: 99%
“…was described to be spherical [113,116]. Raju et al [119] and Yu et al [120] independently observed cubic morphologies of A^Sci-jZr*) precipitates.…”
Section: Ahcscijzr) Phasementioning
confidence: 99%